A survey of tobacco dependence treatment guidelines content in 61 countries - Nilan, Kapka; McNeill, Ann; Murray, Rachael L.; McKeever, Tricia M.; Raw, Martin (Wiley, 2018)
Aims: To assess tobacco dependence treatment guidelines content in accordance with Article 14 of the World Health Organisation (WHO) Framework Convention on Tobacco Control (FCTC) and its guidelines, and association between content and country income level. Design: Cross sectional study. Setting Online survey from March to July 2016. Participants: Contacts in 77 countries, including 68 FCTC Parties, six Signatories and three non-Parties which had indicated having guidelines in previous surveys, or had not been surveyed before. Measurements: A nine item questionnaire on guidelines content, key recommendations, writing and dissemination. Findings:We received responses from contacts in 63 countries (82%); 61 had guidelines. The majority are for doctors (93%), primary care (92%) and nurses (75%). All recommend brief advice, 82% recording tobacco use in medical notes, 98% nicotine replacement therapy (NRT), 61% quitlines, 31% text messaging, 87% intensive specialist support, and 54% stress the importance of healthcare workers not using tobacco. Only 57% have a dissemination strategy, and 62% have not been updated for five or more years. Compared with high income countries, quitlines are less likely to be recommended in upper middle income countries guidelines, OR 0.15 (95% CI 0.04 ‐ 0.61), and intensive specialist support in lower middle income countries guidelines, OR 0.01 (95%CI 0.00 – 0.20). Guidelines updating is positively associated with country income level (p =0.027). Conclusions: Although most tobacco dependence treatment guidelines in the 61 countries assessed in 2016 follow the WHO's Framework Convention on Tobacco Control Article 14 recommendations and do not differ significantly by income level, improvements are needed in keeping guidelines up‐to‐date, applying good writing practices, and developing a dissemination strategy.